Mature plasmacytoid dendritic cells associated with acute myeloid leukemia show similar genetic mutations and expression profiles to leukemia cells. Issue 1 (25th January 2022) - Gong, Xiaoyuan; Li, Chunhong; Wang, Ying; Rao, Qing; Mi, Yingchang; Wang, Min; Wei, Hui; Wang, Jianxiang
Abstract : Introduction: Mature plasmacytoid dendritic cells (pDCs) proliferation associated with myeloid neoplasms (MPDMN) are recognized as a neoplasm related to fully differentiated pDCs. Although it has been reported for many years, the genomic landscape of MPDMN is poorly understood. Methods: We reported two patients who developed acute myeloid leukemia (French-American-British M5 subtype) coexisted with immunophenotypically mature pDCs proliferation, which fit the diagnosis of MPDMN. We sorted pDCs from myeloid blasts by flow cytometry and performed whole-exome sequencing and RNA sequencing of the two cell populations, respectively. Results: The immunophenotypes of pDCs in both patients were positive for CD123 bri, HLA-DR, CD4, CD303, CD304, and negative for CD56, CD34, CD117, and TdT. The variant allele frequency of gene mutations in myeloid blasts and pDCs were similar. The expression data showed myeloid blasts clustered tightly with hematopoietic stem cells, and pDCs from patients clustered tightly with granulocyte-monocyte progenitors/common myeloid progenitor, rather than with pDCs from the GEO platform. Conclusion: Our study suggested that pDCs derived from the leukemic clone, evidenced by a shared mutation profile and similar transcriptional signatures between pDCs and concurrent myeloid blasts.